Hubungan Tingkat Pengetahuan dan Sikap dengan Tindakan Ibu Tentang Pencegahan Demam Berdarah Dengue di Desa Rada Mata - Karolus Wulla Rato; Florensiana Daido; Florentina Kaka; Diana Dorce; Yosep Ngongo; Anselmus Siwa; Yosep Bulu; Yuliana Maghu Ate; Martinus Dama (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
Dengue Hemorrhagic Fever (DHF) is one of the serious public health problems in Indonesia, including in Rada Mata Village. DHF prevention is highly dependent on community behavior, especially housewives, who play an important role in maintaining environmental cleanliness. Objective: This study aims to determine the relationship between the level of knowledge and attitude with maternal actions regarding DHF prevention in Rada Mata Village. Method: This study used an analytical study design with a cross-sectional approach. The sample consisted of 100 mothers selected through purposive sampling technique. Data were collected using a structured questionnaire that measured the level of knowledge, attitude, and DHF prevention actions. Data analysis was performed using the chi-square test. The results showed that there was a significant relationship between the level of knowledge and DHF prevention actions (p = 0.002), as well as between attitude and DHF prevention actions (p = 0.001). Conclusion: The level of knowledge and attitude of mothers is closely related to DHF prevention actions. Efforts are needed to improve education and health promotion for housewives to reduce the incidence of DHF in Rada Mata Village.